Significance of masked and nocturnal hypertension in normotensive women coursing a high-risk pregnancy. Issue 11 (November 2016) - Salazar, Martin R.; Espeche, Walter G.; Leiva Sisnieguez, Betty C.; Balbín, Eduardo; Leiva Sisnieguez, Carlos E.; Stavile, Rodolfo N.; March, Carlos E.; Grassi, Florencia; Santillan, Claudia; Cor, Susana; Carbajal, Horacio A.
Abstract : Objective: The aim was to evaluate the prevalence of nocturnal and masked hypertension and the prognostic values of these blood pressure (BP) abnormalities in normotensive women coursing a high-risk pregnancy. Methods: The study was performed in pregnant women with 20 or more weeks of gestation coursing a high-risk pregnancy, sent to a specialized hypertension department to perform a prospective defined protocol of BP evaluation. Women with office BP at least 140/90 mmHg were excluded. An ambulatory monitoring of BP was performed to identify masked and nocturnal hypertension (defined according to the current guidelines). The adjusted risk for development of preeclampsia/eclampsia (PEEC) was estimated using logistic regression. The ability of SBP and DBP to identify risk of PEEC was estimated using area under the receiver-operating characteristic curves. Results: Eighty-seven women (29 ± 7 years old, 30 ± 5 weeks of pregnancy) were included in this analysis. The prevalence of masked hypertension was 33.3%. Nocturnal hypertension was found in 42.5% of the women. Remarkably, 27.0% of the women with nocturnal hypertension had normal 24-h values according to ambulatory BP monitoring. Twenty-two patients developed PEEC; adjusted relative risks increased with the presence of nocturnal (odds ratio = 4.72, 95% confidence interval 1.25–19.43, P = 0.023) or masked hypertension (odds ratio = 7.81, 95% confidence interval 2.6–22.86, P = 0.001). Nocturnal SBP and DBP had the highest abilities to predict PEEC (area under the curve = 0.77 and 0.80, respectively). Conclusion: Masked and nocturnal hypertension are frequent findings in normotensive women coursing a high-risk pregnancy, and their presence implies an increased risk to develop PEEC.